(untitled) (Journal of the College of Basic Education, 2022)
The aim of the research is to identify the effect of the two methods of teaching inclusion and pairing in learning some football skills, and which methods are used best.The researcher used the experimental method due to its suitability to the nature of the research. The research sample consisted of students in the first stage of the College of Physical Education / Al-Mustansiriya University, whose number is (40) students, with a rate of (20) students for each group, as the first experimental group was studied by the method of inclusion and the second by the method of peer teaching, and equivalence was made between the members of the groups in the variables (age, height, weight) and the research tools were specific skill tests in football (driving, handling, scoring).